2016
DOI: 10.1073/pnas.1524578113
|View full text |Cite
|
Sign up to set email alerts
|

Spectral discrimination in color blind animals via chromatic aberration and pupil shape

Abstract: We present a mechanism by which organisms with only a single photoreceptor, which have a monochromatic view of the world, can achieve color discrimination. An off-axis pupil and the principle of chromatic aberration (where different wavelengths come to focus at different distances behind a lens) can combine to provide "colorblind" animals with a way to distinguish colors. As a specific example, we constructed a computer model of the visual system of cephalopods (octopus, squid, and cuttlefish) that have a sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…The retina acts as a monochrome image sensor, when the detection plane is in a specific position, the image of a point object of different radiation wavelengths at the distance of infinity exhibits different degrees of dispersion, diagrammatic drawing of the images can be seen in Figure 1d. Through contrast analysis of chromatic blur images, spectral discrimination can be obtained under certain conditions, which is a probable perception mechanism of chromatic blur vision in color blind animals [7]. Inspired by the studies of Stubbs et al, we believe that the chromatic blur can be used to form a hyperspectral imaging technology.…”
Section: Eyeball Modelmentioning
confidence: 93%
See 3 more Smart Citations
“…The retina acts as a monochrome image sensor, when the detection plane is in a specific position, the image of a point object of different radiation wavelengths at the distance of infinity exhibits different degrees of dispersion, diagrammatic drawing of the images can be seen in Figure 1d. Through contrast analysis of chromatic blur images, spectral discrimination can be obtained under certain conditions, which is a probable perception mechanism of chromatic blur vision in color blind animals [7]. Inspired by the studies of Stubbs et al, we believe that the chromatic blur can be used to form a hyperspectral imaging technology.…”
Section: Eyeball Modelmentioning
confidence: 93%
“…With respect to a photographic imaging system with large imaging chromatic aberrations, the resulting images typically exhibit varying degrees of blur. Stubbs et al [7] further found that the semi-annular off-axis pupil or large circular pupil of the octopus can cause a high lateral chromatic aberration. Under the premise that the lens has a certain longitudinal chromatic aberration at the same retinal position, higher lateral chromatic aberration will occur with a semicircular off-axis pupil than a small on-axis circular pupil, such as the pupil of a human eye, thereby further aggravating the degree of image blur.…”
Section: Eyeball Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…In nature, light sensing molecules are found in colour-changing cephalopod skin [31,40]. Cephalopods have also evolved special pupils [45] to sense the colour and pattern of their background. Specialised low-cost, bio-inspired light sensors could be developed for camouflage and could be activated and actuated by the background light.…”
Section: New Materials and Technologies To Platform Invisibilitymentioning
confidence: 99%